The Armadollar-Petrodollar Coalition and the Middle East - Robin Rowley; Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 1989)
This is the third paper in a series of four essays that deal with recent developments affecting the political economy of armaments. It begins by identifying the `military bias paradox' of divergent behaviour, whereby the large armament corporations experienced an almost uninterrupted growth since the peak of the Vietnam War while domestic military spending exhibited a decade-long decline. The resolution of this apparent paradox could be found in the merging institution of arms exports, which supplemented domestic military budgets. The expansion of world markets for weapons coincided with the oil crisis of the 1970s. The Middle East became the focus of these developments. The interaction during the 1970s of rising military exports to this area and growing oil exports from the region provided a bsais for cooperation between major armament and energy corporations in an `Armadollar-Petrodollar Coalition'. The consolidation of this coalition removed a major conflict between `civilian' and `military' producers in the United States and affected the course of U.S. domestic and foreign military policies.
Keywords: 330; arms exports; arma-core; corporation; elite; free flow; foreign policy; institutionalized waste; limited flow; Middle East; Asia; military spending; oil; petro-core; petrodollars; profit; redistribution; ruling class; Vietnam War; United States